2011
DOI: 10.1371/journal.pone.0027191
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport of Bile Acids Decreases Mucin 2 in Neonatal Ileum: Implications for Development of Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is the most common gastrointestinal emergency of premature infants, but its etiology remains unclear. We have previously shown that mucin 2 (Muc2) positive goblet cells are significantly decreased in NEC. We have also shown that ileal bile acids (BAs) are significantly increased during the development of this disease. Because BAs can affect mucins, we hypothesized that elevated ileal BAs contribute to decreased Muc2 in experimental NEC. The role of Muc2 in NEC was evaluated in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…In agreement with the postulated role of increased BS uptake in the distal small intestine, ASBT expression (mRNA and immunohistochemistry) was increased in intestinal samples of preterm infants with NEC in comparison to ileal samples taken during surgery on preterm infants with other diseases [6]. Furthermore, BSs have been shown to decrease ileal mucin production more profoundly in immature than in older ileums, and alter the intestinal mucus layer which might compromise the intestinal barrier function [7]. …”
Section: Introductionmentioning
confidence: 54%
“…In agreement with the postulated role of increased BS uptake in the distal small intestine, ASBT expression (mRNA and immunohistochemistry) was increased in intestinal samples of preterm infants with NEC in comparison to ileal samples taken during surgery on preterm infants with other diseases [6]. Furthermore, BSs have been shown to decrease ileal mucin production more profoundly in immature than in older ileums, and alter the intestinal mucus layer which might compromise the intestinal barrier function [7]. …”
Section: Introductionmentioning
confidence: 54%
“…In both humans 87,88 and rats 76 with NEC, the number of mucin 2 and trefoil factor 3 goblet cells is significantly reduced and mice with genetically aberrant mucin 2 develop more severe disease than those with normal mucin. 89 In addition, ileal BAs, increased in NEC and associated with disease severity, decrease ileal mucin levels in neonatal but not adult ileum, 89 data which indicate a possible mechanism for development of NEC in premature infants. Zhang et.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…It has been suggested that increased luminal bile acids [165], abnormal bile acid metabolism [147] and dysregulated bile acid transporters [166, 167] contribute to NEC via dampening goblet cell differentiation and decreasing mucin Muc2 expression in premature ileum [148]. We further showed that bile acids activated Notch signaling plays a role in the development of NEC [66].…”
Section: Cellular Regulation Of Tlr4 Signaling As a Therapeutic Targementioning
confidence: 63%
“…In seeking to understand the mechanisms by which TLR4 regulates enterocyte differentiation, TLR4 deletion was found to suppress Notch signaling in the small intestinal epithelium, which resulted in increased goblet cell differentiation and decreased NEC severity [66]. Interestingly, bile acids, which are significantly increased during the development of NEC [147] and are associated with reduced goblet cells and decreased mucin Muc2 expression in premature ileum [148], are significantly reduced in TLR4 ΔIEC mice and TLR4 knockout mice [66]. …”
Section: Tlr4 Signaling In Epithelial and Endothelial Cells Is Requirmentioning
confidence: 99%